(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Effective face mask ventilation (FMV) is a critical component of safe airway management during induction of general anaesthesia. Neuromuscular blockade (NMB) is routinely used to facilitate tracheal intubation; however, its effect on mask ventilation and tidal volume delivery remains variable and clinically important. This study evaluates the impact of neuromuscular blockade on tidal volume changes during FMV. Methodology: This prospective observational study was conducted in 87 adult patients aged >18 years of ASA physical status I and II undergoing elective surgeries under general anaesthesia requiring neuromuscular blockade. Patients with anticipated difficult airway, BMI >35 kg/m², respiratory disease, or neuromuscular disorders were excluded. After induction of anaesthesia, baseline tidal volumes were recorded during mask ventilation, followed by administration of vecuronium (0.1 mg/kg). Tidal volume measurements were repeated after confirmation of neuromuscular blockade using train-of-four monitoring. Data were analysed using SPSS software, and statistical significance was set at p<0.05. Results: Most patients were females (58.6%) and overweight/obese (65%). Majority had Mallampati class II and Grade 1–2 mask ventilation before NMB. Following neuromuscular blockade, tidal volume showed significant improvement in a subset of patients, while others demonstrated minimal change. Overall, ventilation remained stable and no cases of complete ventilation failure were observed. Conclusion: Neuromuscular blockade influences tidal volume during FMV and may improve ventilation in selected patients. Careful assessment is essential before administration to ensure airway safety during induction.